Relationship Between Menstrual Pain (Dysmenorrhea) And Quality Of Life Sleep In Adolescent Girls At SMA Negeri 1 School West Daha, Hulu Sungai Selatan Regency - Nadia, Nadia; Sri Sunaringsih Ika Wardojo; Nikmatur Rosidah (Sean Institute, 2024)
Dysmenorrhea is an imbalance of the hormones progesterone, prostaglandin and psychological factors which results in pain during menstruation, thus causing nursing problems and affecting basic human needs, one of which is sleep. This research was conducted at the SMAN 1 Daha Barat school, Hulu Sungai Selatan Regency. The aim of this study was to determine the relationship between menstrual pain (dysmenorrhea) and sleep quality in adolescent girls at SMAN 1 Daha Barat, Hulu Sungai Selatan Regency. This type of research is quantitative research with a cross sectional approach. Sampling in this study was based on a purposive sampling technique with a sample size of 50 people. Data was collected using the Numerical Rating Scale (NRS) questionnaire to measure menstrual pain and the Pittsburgh Sleep Quality Index (PSQI) to measure sleep quality. The research results from 50 respondents: 11 respondents (22.0%) experienced mild pain, 27 respondents (54.0%) had moderate pain, and 12 respondents (24.0%) experienced severe pain. A total of 16 respondents (32.0%) had a good sleep quality category, and 34 respondents (68.0%) had a poor sleep quality category. The chi square test results obtained a significance value of 0.004 (<0.005), which means there is a relationship between menstrual pain (dysmenorrhea) and sleep quality in young women at SMAN 1 Daha Barat Kab. Hulu Sungai Selatan.